2014
DOI: 10.1115/1.4029462
|View full text |Cite
|
Sign up to set email alerts
|

Cohesive Zone Model for the Interface of Multiwalled Carbon Nanotubes and Copper: Molecular Dynamics Simulation

Abstract: Due to their superior mechanical and electrical properties, multiwalled carbon nanotubes (MWCNTs) have the potential to be used in many nano-/micro-electronic applications, e.g., through silicon vias (TSVs), interconnects, transistors, etc. In particular, use of MWCNT bundles inside annular cylinders of copper (Cu) as TSV is proposed in this study. However, the significant difference in scale makes it difficult to evaluate the interfacial mechanical integrity. Cohesive zone models (CZM) are typically used at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…A number of published studies have reported that a CNT-Cu composite material could have several advantages over any of the individual materials. Results from molecular dynamics simulations predict that the addition of CNTs can dramatically decrease the skin effect of copper and show strong van der Waal (vdW) interfacial bonds to copper [28,29]. Subramanian et al [30] synthesized a novel CNT-Cu composite film using electroplating, and showed a hundredfold increase in ampacity when compared with Cu.…”
Section: Introductionmentioning
confidence: 99%
“…A number of published studies have reported that a CNT-Cu composite material could have several advantages over any of the individual materials. Results from molecular dynamics simulations predict that the addition of CNTs can dramatically decrease the skin effect of copper and show strong van der Waal (vdW) interfacial bonds to copper [28,29]. Subramanian et al [30] synthesized a novel CNT-Cu composite film using electroplating, and showed a hundredfold increase in ampacity when compared with Cu.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular interactions at the interfaces between CNTs and the PDMS matrix in ReaxFF can affect changes in distance between CNTs when uniaxial tension is applied to a molecular structure. 44 The MD simulations are conducted at different energy tolerances of 1.00E-3, 1.00E-4, and 1.00E-5 43 with varying the values of the strain increments of 0.01, 0.006, and 0.004 to consider the effect of the molecular interactions and appplied loading rate on changes in distance. 43 The average distance was obtained by averaging the three distances between CNTs in the MD simulations.…”
Section: Parameter and Condition Simulationmentioning
confidence: 99%
“…Figure 3 provides the average distance between CNTs against the strain in CNT/PDMS nanocomposites under uniaxial tension along the x ‐direction. The molecular interactions at the interfaces between CNTs and the PDMS matrix in ReaxFF can affect changes in distance between CNTs when uniaxial tension is applied to a molecular structure 44 . The MD simulations are conducted at different energy tolerances of 1.00E‐3, 1.00E‐4, and 1.00E‐5 43 with varying the values of the strain increments of 0.01, 0.006, and 0.004 to consider the effect of the molecular interactions and appplied loading rate on changes in distance 43 .…”
Section: Numerical Parametric Studiesmentioning
confidence: 99%
“…However, there has been debate over how far virial stress expresses mechanical stress [38][39][40][41][42][43][44]. As concluded from a previous study [45], since stresses were time-averaged for all times and nearest image convention boundary conditions are activated in the stress calculation direction (y-direction), mechanical stress could be represented by virial stress when the kinetic part is ignored. This is given in the following:…”
Section: Pull-out In the Normal Directionmentioning
confidence: 99%